2021
DOI: 10.1007/s15010-021-01672-z
|View full text |Cite
|
Sign up to set email alerts
|

In-depth profiling of COVID-19 risk factors and preventive measures in healthcare workers

Abstract: Purpose To determine risk factors for coronavirus disease 2019 (COVID-19) in healthcare workers (HCWs), characterize symptoms, and evaluate preventive measures against SARS-CoV-2 spread in hospitals. Methods In a cross-sectional study conducted between May 27 and August 12, 2020, after the first wave of the COVID-19 pandemic, we obtained serological, epidemiological, occupational as well as COVID-19-related data at a quaternary care, multicenter hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 40 publications
(47 reference statements)
1
24
1
Order By: Relevance
“…Within the frames of the longitudinal Care Corona Immune Study (CCI; 4 study visits; N = 220) and the cross-sectional All Corona Care Study (ACC; N = 7546) performed towards the end of the first wave, we conducted several epidemiological psychosocial analyses. 15 , 16 …”
Section: Resultsmentioning
confidence: 99%
“…Within the frames of the longitudinal Care Corona Immune Study (CCI; 4 study visits; N = 220) and the cross-sectional All Corona Care Study (ACC; N = 7546) performed towards the end of the first wave, we conducted several epidemiological psychosocial analyses. 15 , 16 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated workplace exposure to be a risk for COVID-19 transmission among healthcare workers and patients 22 , 23 , 24 , 25 , 26 . While there are no specific prior articles evaluating the risks of COVID-19 exposure in sonographers, it has been demonstrated that there is an increased risk for transmission for nurses, staff working on COVID units, and those who have high risk exposures 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Nurses, particularly those in the intensive care units, are at the highest risk for COVID-19 infections among all HCWs [40] , [41] . Contrary to these findings, we found a higher estimated risk for infections among physicians.…”
Section: Discussionmentioning
confidence: 99%